Implementasi Pendidikan Karakter dalam Konsep Pendidikan Muhammadiyah - Akhmad, Fandi (Universitas Ahmad Dahlan, 2020)
The purpose of this study was to describe the implementation of character education in the concept of Muhammadiyah education in SD Muhammadiyah Kademangaran, Tegal Regency. Tegal. Educational concept in Muhammadiyah pioneered by KH. Ahmad Dahlan uses holistic education. Education that combines general education and religion in one curriculum. Holistic education is expected to be able to make students have cognitive and spiritual abilities, which make students competent in general and religious abilities. KH character education. Ahmad Dahlan is forming Muslim people who are noble minded, wide-sighted and understand worldly science issues and are willing to fight for the progress of society at large. The concept of Muhammadiyah education is centered into four things that must be interrelated, namely schools, families, communities and mosques. Data collected through interviews with information sources, observations, and documentation studies will be analyzed qualitatively and presented descriptively. Based on the results of the descriptive analysis it was revealed that (1) the implementation of character education through the concept of Muhammadiyah education in SD Muhammadiyah Kademangaran Tegal Regency through the integration of the four Muhammadiyah education centers has not been fully carried out in integration with families. (2) the effectiveness of character education programs in the concept of Muhammadiyah education needs to be improved in terms of the integration between education in the school environment and the family environment. In addition, in the community environment, the Muhammadiyah Kademangaran Elementary School in Tegal Regency is still cooperating with Muhammadiyah people only, while the general public is still not integrated (3) The constraints faced in the implementation of character education in the Muhammadiyah concept in the Muhammadiyah Elementary School in Tegal Regency are many student guardians or student guardians who simply hand over their children's education to the school in this case SD Muhammadiyah Kademangaran Tegal Regency